Examining patterns of multivariate, longitudinal symptom experiences among older adults with type 2 diabetes and cancer via cluster analysis. Issue 6 (December 2015) - Hershey, Denise Soltow; Pierce, Steven J.
Abstract: Purpose: Diabetes and cancer are chronic conditions that produce symptoms, some unique to each condition and others common to both. Previous studies have reported on subgroups of patients who experience distinct combinations of symptoms in cross-sectional samples and the univariate longitudinal trajectories of individual symptoms. The literature currently lacks examples of research that take a multivariate longitudinal perspective to understanding patients' symptom experiences. The purpose of this study was to identify subgroups of patients who share distinct multivariate longitudinal profiles with respect to how symptom severity changes over time for a set of five symptoms (pain, fatigue, change in appetite, nausea, and numbness and tingling). Methods: This exploratory study included 43 participants with pre-existing diabetes from eight community-based cancer centers who were receiving chemotherapy for a solid tumor. Using baseline and 8-week data, a model-based cluster analysis with Bayesian regularization was used to identify subgroups. Results: Two groups were identified. Group 1 experienced mild symptoms that changed very little at 8 weeks; group 2 experienced mild to moderate symptom severity, with small increases in fatigue, nausea, and numbness and tingling. Effect size confidence intervals suggest that level of depression, length of time with diabetes, and severity of diabetes at baseline may differ between groups. Conclusions: More research in this area is needed to further test this model, address limitations associated with analyzing a small sample, and explore factors that may be associated with changes in the overall symptom experience for patients with diabetes and cancer. Highlights: Two distinct groups were identified. Group 1 experienced mild symptoms that changed very little at 8 weeks; group 2 experienced mild to moderate symptom severity, with small increases in fatigue, nausea, and numbness and tingling. Effect size confidence intervals suggest that level of depression, length of time with diabetes, and severity of diabetes at baseline may differ between groups. Individuals with more depression, had diabetes longer and higher levels of diabetes severity had more changes in symptoms over time, particularly numbness and tingling.